Tessellated Scale Eucalymnatus tessellatus (Signoret) - Adriana Espinosa; Amanda Hodges; Greg Hodges; Forrest Howard; Catharine Mannion (EDIS)
EENY456, a 4-page illustrated fact sheet by Adriana Espinosa, Amanda Hodges, Greg Hodges, Forrest Howard, and Catharine Mannion, is part of the Featured Creatures collection. It describes this soft scale, native to South America, that can be a pest in greenhouses, commercial nurseries, and in the south Florida landscape — distribution, field characteristics, life cycle, hosts, general plant damage, and management. Includes references. Published by the UF Department of Entomology and Nematology, July 2009.